1978
DOI: 10.1128/iai.19.1.239-245.1978
|View full text |Cite
|
Sign up to set email alerts
|

Limits of rickettsial infectivity

Abstract: Seven species of pathogenic rickettsiae were compared in five assay systems for group, species, strain, and phase differences in infectivity. The species examined include Rickettsia prowazekii (Breinl and Cairo 3 strains), R. typhi, R. canada, R. rickettsii (Sheila Smith and R strains), R. conorii, R. sibirica, and Coxiella burnetii in phases I and II. Pathogenicity was characterized in terms of fever in guinea pigs. All comparisons of infectivity and pathogenicity were described in terms of numbers of rickett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 21 publications
5
35
0
Order By: Relevance
“…The results obtained for milk samples from 21 cows proved that the system could detect coxiellae in naturally infected specimens. This is important as C. burnetii is a strictly intracellular agent (16). Findings obtained with artificially contaminated samples containing only extracellular C. burnetii particles cannot simply be transferred to clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained for milk samples from 21 cows proved that the system could detect coxiellae in naturally infected specimens. This is important as C. burnetii is a strictly intracellular agent (16). Findings obtained with artificially contaminated samples containing only extracellular C. burnetii particles cannot simply be transferred to clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas animals in general show no clinical signs of infection except occasional abortions and other problems with reproduction, C. burnetii can cause serious illness in humans. This agent is very resistant to environmental influences, and even a single infective particle can initiate an infection in the animal model (16).…”
mentioning
confidence: 99%
“…Embryonated chicken egg yolk sacs have been widely used in the past (39), but they are now being replaced by cell culture systems. Inoculation into guinea pigs has also been widely used (66,103). The mouse is the species of choice for the isolation of R. akari, Rickettsia australis, and especially O. tsutsugamushi.…”
Section: Isolation Of Rickettsiaementioning
confidence: 99%
“…By way of comparison, earlier studies in Hartley guinea pigs (Ormsbee et al, 1978) showed that only two viable C. burnetii (phase 1) cells would produce a fever, a similar sensitivity to the SCID mouse spleen assay.…”
Section: Discussionmentioning
confidence: 97%